2021
DOI: 10.1093/cid/ciab222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of National Adoption of Treat-All Guidelines on Pre-Antiretroviral Therapy (ART) CD4 Testing and Viral Load Monitoring After ART initiation: A Regression Discontinuity Analysis

Abstract: Background The World Health Organization’s Treat-All guidance recommends CD4 testing prior to antiretroviral treatment (ART) initiation, and routine viral load (VL) monitoring (over CD4 monitoring) for patients on ART. Methods We used regression discontinuity analyses to estimate changes in CD4 testing and VL monitoring among 547,837 ART-naïve patients enrolling in HIV care during 2006-2018 at 225 clinics in 26 countries wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Our study and the recent global IeDEA study used IeDEA data and regression discontinuity design, however the latter study pooled data within broad income-group classifications that likely obscured heterogeneity among countries [12]. Further, the absence in the global study of Zambia, which comprised nearly 85% of low and lower-middle income data in our study and had the most divergent results, may further explain dissimilar findings.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Our study and the recent global IeDEA study used IeDEA data and regression discontinuity design, however the latter study pooled data within broad income-group classifications that likely obscured heterogeneity among countries [12]. Further, the absence in the global study of Zambia, which comprised nearly 85% of low and lower-middle income data in our study and had the most divergent results, may further explain dissimilar findings.…”
Section: Discussionmentioning
confidence: 67%
“…The effect of Treat-All on pre-ART CD4 testing varied in Southern Africa. Although a recent global IeDEA study found Treat-All adoption in low or lower-middle income countries led to an immediate decline in pre-ART CD4 testing among adults who enrolled in HIV care after Treat-All adoption [12], we found considerable heterogeneity in the direction and magnitude of the immediate effect in such countries [33], which also varied by sex. We found testing slightly increased in Zambia, but decreased substantially in Malawi and moderately in Mozambique, with no effect in Lesotho or Zimbabwe.…”
Section: Main Findingsmentioning
confidence: 61%
See 3 more Smart Citations